Adjectival Modification in Truku Seediq - Saillard, Claire (Language and Linguistics, 2019)
This paper investigates the position of adjectives in noun phrases in Truku Seediq, proposing that the two documented positions correspond to different semantics as well as a difference in syntax. While post-nominal adjectives, corresponding to basic word-order in Truku Seediq, may be either restrictive or descriptive, pre-nominal adjectives, seen as an innovation, are semantically restrictive. This paper also argues for a difference in syntactic structure for both kinds of adjectives, restrictive adjectives heading their own projection while descriptive adjectives are bare adjectives standing in a closer relationship to the modified noun. This paper further identifies a syntactic constraint for pre-nominal adjectival placement that applies regardless of restrictivity of the modifier, namely the presence of a possessive clitic to the right of the modified noun. Data collection is achieved through both a traditional elicitation method and an experimental task-based method. Data are further digitalized in order to ensure systematic searchability. The data thus collected are apt to support semantic analysis as well as an investigation of age-group-related variation. It is claimed that language contact with Mandarin Chinese may be one of the triggering factors for the development of a pre-nominal position for modifying adjectives in Truku Seediq.
Keywords: adjectives; language contact; restrictive modification; syntactic position; Truku Seediq